2020
DOI: 10.4046/trd.2020.0039
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Evaluation of Non-Interpretable Results Associated with rpoB Gene in Genotype MTBDRplus Ver 2.0

Abstract: Background: Line probe assay (LPA) is standard diagnostic tool to detect multidrug resistant tuberculosis. Noninterpretable (NI) results in LPA (complete missing or light wild-type 3 and 8 bands with no mutation band in rpoB gene region) poses a diagnostic challenge. Methods: Sputum samples obtained between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…One patient with negative BD MAX and positive phenotypic DST results for RIF resistance also showed negative LPA results for RIF resistance. The causes of false-negative results of molecular methods for RIF resistance have rarely been studied, but previous studies have suggested that some strains with S531W and S531F mutations within the rpoB gene are non-interpretable via LPA [ 27 ], and some strains with L533P mutation susceptible via Xpert [ 28 ]. Additionally, approximately 4% of RIF resistances are caused by mutations outside the rpoB gene [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…One patient with negative BD MAX and positive phenotypic DST results for RIF resistance also showed negative LPA results for RIF resistance. The causes of false-negative results of molecular methods for RIF resistance have rarely been studied, but previous studies have suggested that some strains with S531W and S531F mutations within the rpoB gene are non-interpretable via LPA [ 27 ], and some strains with L533P mutation susceptible via Xpert [ 28 ]. Additionally, approximately 4% of RIF resistances are caused by mutations outside the rpoB gene [ 29 ].…”
Section: Discussionmentioning
confidence: 99%